Posttraumatic stress and depression in Yazidi refugees - Nasıroğlu S; Çeri V (Neuropsychiatric Disease and Treatment, 2016)
Serhat Nasıroğlu,1 Veysi Çeri2 1Department of Child and Adolescent Psychiatry, Faculty of Medicine, Sakarya University, Sakarya, Turkey; 2Pendik Training and Research Hospital, Department of Child and Adolescent Psychiatry, Medical School of Marmara University, Istanbul, Turkey Aim: The aim of this investigation was to determine the frequency of mental pathologies in children and adolescents of the Yazidi minority group who immigrated to Turkey from Iraq. The refugees were asked about preventive and risk factors that occurred before and after their immigration. Subjects and methods: The sample comprised 55 children and adolescents (30 males and 25 females) who were Yazidi refugees and had settled in the Uçkuyular, Oğuz, Onbaşi, and Uğurca villages of Batman, Turkey. The study was conducted 9 months after the refugees had immigrated. The participants were evaluated in their native language through a semistructured interview titled “Reliability and Validity of Schedule for Affective Disorders and Schizophrenia for School-Age Children – Present and Lifetime Version – Turkish Version”. A sociodemographic form was prepared so that investigators could understand their traumatic experiences before and after the migration and their current social conditions. All the interviews were conducted in the participants’ native language without the help of translators. The investigators filled out the sociodemographic forms. Results: Posttraumatic stress disorder (PTSD) was detected in 20 children (36.4%), depression in 18 (32.7%), nocturnal enuresis in six (10.9%), and anxiety in four (7.3%). The following factors were found to be associated with depression: witnessing violence and/or death, being a girl, having older parents, being the elder child, and having multiple siblings (P<0.05). Risk factors for PTSD, depression, and comorbid conditions included witnessing violence and/or death (P<0.05). Four participants were observed to have both PTSD and depression (7.3%). Conclusion: Most of the refugee children had experienced serious traumatic events in their home country. PTSD, depression, and comorbid mental problems are frequently seen in refugee children. Keywords: refugees, child and adolescent, PTSD, depression, risk factors